NOVÉ NA STARÉ – Brno, nároží Bratislavská - Stará - Vávra, Vít (Vysoké učení technické v Brně. Fakulta architektury)
nové na staré pro mladé i staré, chudé i bohaté

new on old place for young and old, poor and rich
NEW ON THE „OLD“ – Brno, Bratislavská - Stará Corner
Keywords: nové na staré pro mladé i staré; chudé i bohaté; new on old place for young and old; poor and rich